Decoding the Suprasegmental Aspect: A Deep Dive into Word Stress Errors in English Pronunciation - Nuraini, Latifah; Hastini, Hastini; Sudarkam R. Mertosono (Journal of General Education and Humanities, 2024)
In pronunciation, students encounter significant challenges when it comes to stress. The majority of students often struggle with the accurate placement of stress in words. This research project seeks to identify the key aspects: the specific word categories that pose the most significant difficulty for students regarding stress placement, the syllable position where students commonly struggle with pronunciation, and the predominant types of errors made when attempting to pronounce stress in English. This research takes a quantitative descriptive approach to gather information about these three aspects. The study's target population consists of 250 students from Tadulako University, with a sample of 35 students chosen through purposive sampling. Data collection was carried out through tests and mobile phones as research instruments, and the data were subsequently analyzed using basic statistical methods within the Excel application. The findings reveal that verbs are the most challenging for students to pronounce among various word categories, with 53 errors observed. Regarding syllable position, the ultimate position is the most difficult for students regarding placing stress on pronunciation, with 20 errors recorded. In line with the linguistic category, the error was identified in verb (48%), noun (25 %), and adjective (27%) errors produced by students.